Legal Review of Criminal Acts of Defamation Through Social Media Based on Justice Values - Hargiharso, Muhammad Dimas; Laksana, Andri Winjaya (Jurnal Hukum Khaira Ummah, 2025)
The development of information technology has brought significant changes in the way people interact, especially through social media. However, the ease of expressing opinions in digital spaces has also given rise to new legal problems, one of which is the crime of defamation. This study aims to analyze how positive legal provisions in Indonesia regulate defamation through social media and how the application of these laws can reflect the values of justice. This study uses a normative legal approach with secondary data in the form of laws and regulations, literature, and related court decisions. Based on the results of the analysis, it was found that the provisions in Article 27 paragraph (3) of the ITE Law often give rise to multiple interpretations and have the potential to violate the principle of substantive justice. Law enforcement against cases of defamation through social media has not fully considered the context and motives of the perpetrators, and has not been optimal in protecting the rights of victims and suspects. In many cases, a repressive approach is preferred over a restorative approach. Therefore, there needs to be legal reform and reinterpretation of norms so that the law is not only legalistic, but also reflects the values of social justice. The conclusion of this study confirms that the regulation and application of law against criminal acts of defamation on social media must be aligned with the principles of justice, proportionality, and protection of human rights. Regulatory reform and digital education for the public are strategic steps to achieve a fair and balanced legal system in the digital era.